Inherited multicentric osteolysis: case report of three siblings treated with bisphosphonate - Whitewood Colin; Lee Senq-J; Murray Kevin J (BMC, 2010)
Abstract Inherited Multicentric Osteolysis (IMO) is an uncommon familial condition of idiopathic pathophysiology causing bone osteolysis and dysplasia. These patients present with common rheumatologic complaints of pain, dysfunction and disability, and are often initially misdiagnosed as a chronic rheumatic disease of childhood such as juvenile idiopathic arthritis. We report a case of three siblings diagnosed with IMO. Diagnosis was made during childhood, with each sibling having different manifestations and course of disease. One had a previous history of bilateral hip dysplasia. Two had osteolysis of the foot, distal tibia and femur (lower limb bones), whilst one had osteolysis of the rib and unusual clavicular fractures. Unusually, all siblings appear to experience decreased pain sensation compared to norms. All siblings were treated with bisphosphonates and experienced a rapid improvement in pain symptoms, decreased analgesic requirements. Two had bone mineral density testing performed and both had increases post-bisphosphonate. In all three, there was subjective evidence of stabilisation of bone disease. Testing for matrix metalloproteinase-2 (MMP2) gene was negative.